Intelligent Push-Pull Devices for Manipulation of Slung Loads - Welch, Hogan; Mohan, Shankar; Santillo, Mario; Mazumdar, Anirban (IEEE robotics and automation letters, 2022)
Industrial facilities can benefit from lift assist devices to reposition heavy payloads. Existing solutions suffer from drawbacks, particularly when used for precise positioning of heavy loads. This work presents a new human-centric approach that pairs an intelligent push-pull device with a bridge crane to allow a human operator to manipulate the payload. The combined system leverages force feedback from the device to command the crane, allowing the human operator to simultaneously impose stabilizing forces and dictate the payload velocity. The core contributions of this paper are 1) outlining a human-centric method for collaborative positioning of slung loads, 2) creating a computational model for our system behavior, 3) providing quantitative performance data from a precise positioning experiment with 7 human subjects, and 4) demonstrating how the new method provides statistically significant reductions in the integrated force (impulse). The mean impulse saw a reduction from 22.51 N · {} s when using traditional joystick control to a mean impulse of 11.56 N · {} s when using our intelligent push-pull device.